Analysis by Monte-Carlo simulation of uncapped nanocrystals density effects on the collection efficiency. (September 2017) - Doan, QuangTri; El Hdiy, Abdelillah; Duong, Xuan-Nui; Duong, Chinh-Cuong; Nguyen, Luong-Thien
Abstract: The effects of nanocrystals density on the electron beam induced current are studied by the use of Monte-Carlo simulation. The nanocrystals are considered as recombination centers for captured charges and are distributed randomly at the sample surface. The induced current is collected by a nanocontact. The surface recombination velocity at the free surface is supposed to be zero. For a given electron beam energy, simulated results show a decrease of the carrier collection efficiency and shrinkage of its profile when the nanocrystals density increases. As a consequence, the minority carrier effective diffusion length which is extracted from simulated results is a decreasing function. This is not surprising because it is well known that an increase of recombination centers leads to reduction of the minority carrier lifetime and then a reduction of their diffusion length. These effects are highlighted because of both collecting electrode small size and perpendicular configuration. Highlights: Monte-Carlo simulation of the nano-EBIC technique. Random distribution of uncapped nanocrystals at the surface. Carrier trapping process in nanocrystals and its effects on the nano-EBIC current.